POLEMIK BUDAYA DAN CINTA : DISKRIMINASI PENDAMPING HIDUP PEREMPUAN BERKASTA TINGGI - Muh. Adnan Malewa (Fakultas Ilmu Budaya universitas Hasanuddin, 2019)
High-caste women in Bali are sometimes not considered subalterns, because they have economic, symbolic and social capital that distinguishes them from Sudra-caste women. In fact, women of high caste have complex problems in choosing their life partners, due to disciplining of cultural capital in the form of tradition. The production of traditions which become a single truth and cannot be separated from control of knowledge and power, thus binding them to the circle of power itself. They are in a space where Culture and Love are the dilemma. Choosing a marriage partner according to caste tradition, or becoming part of modernization to be free to choose with her will. In this research, the writer uses conventional ethnographic methodology with qualitative sources. Key informants in this research will focus on high-caste women. Theory of Power and knowledge Relations from Foucault became the main theory, for looking at the discipline and bond of power and knowledge in the traditions of the Balinese. Assisted by Bourdiue's structuration theory to see the ambivalence of cultural capital that associated in the tradition of Balinese life companion choice. This analysis will produce a new perspective study of gander, to seeing the manipulation of power inside Balinese tradition which curbs the dominance of capital in shaping women with power modality as subaltern. Keywords: Caste, Subaltern, Feminism, Bali